Energy efficient lighting for better environment - Mohd Ariffin, Noor Aziah; Maikano, Ahmad Abdullahi (2015)
Global overall energy consumption is rising. Along with it, a relative contribution is lighting energy. While existing light sources are reaching their limit of performance, LED-based light sources are however offering the potential to meet energy saving targets with their improving performance. In most buildings, the dominant light source is the fluorescent lamp. Although it is energy efficient, the total energy consumed is still significant, especially more so for public institutional buildings in Malaysia. This research studied the application of linear LED replacement tubes as the alternative retrofitting energy efficient solution to the existing fluorescent tubes in the International Islamic University Malaysia Main Library. The study assessed the potential to reduce energy consumption and consequently, the electricity bill but without reducing the performance. The methodology adopted the data collection technique through physical walk-through audit and an observational survey of the existing lighting situation. Using the Lighting Power Density (LPD) calculation methods from ASHRAE and IESNA, a recommended light level and cost analysis were undertaken. With the LED retrofit, the recommended lighting levels were established, and an annual savings of 33% was predicted in one academic building, with a return on investment period of less than two years.